Analysis Knowledge of Spiritual Care and HbA1c Among Individual Living with Diabetes Mellitus - Agustina, Dwi; Dewi, Ratna Sari; Makajil, Johari Daud (Fundamental and Management Nursing Journal, 2025)
Introduction: Diabetes mellitus (DM) is a metabolic disease represented by hypoglycemia due to abnormalities in insulin secretion, insulin action, or both. Normal blood glucose levels influence the healing process for DM complications. Reducing blood glucose levels can be achieved by releasing the hormone endorphin, secreted when the patient is calm and comfortable. One way to achieve self-calm is by getting spiritual care. Spiritual care is a process of healing by fulfilling spiritual needs. The objective assessment of DM is seen in hematological parameters, one of them is Glycate Haemoglobin (HbA1c). This study to identifying the analysis between the knowledge of spiritual care and HbA1c assessment. Methods: This was a quantitative research correlation analysis design using person correlation. The dependent variable is the patient's knowledge of spiritual care, while the independent variable is HbA1C levels. The sample is 32 from 115 DM patients with new cases in RSUD Cibinong, Bogor 2022. questionnaire used to collect the knowledge of spiritual care and HbA1c assessment was taken at the same time. Results: The results showed that the majority were female (68.8%), aged 56-65 years (46.9%), knowledge level high category (56.3%), and HbA1c levels were normal (81.3%.) Bivariate analysis has significant results in identifying the relationship between the knowledge of spiritual care and HbA1c levels in DM patients (p-value 0.02). Conclusions: This study concludes that spirituality care can influence HbA1c assessment to a normal level. Spirituality care could be non-pharmacological therapy for DM patients.